Tactical refereeing and signaling by publishing - Sergey V. Popov (Cardiff University, Cardiff Business School, 2022)
A peer review is used ubiquitously in hiring, promotional, and evaluation decisions, within academia and beyond. It is usually conducted to allocate limited resources, such as the budget of a funder or the pages of a journal. With limited capacity, a peer review may lead to negatively biased evaluations precisely because approving a peer's worthy project lowers the chance that a referee's own project will be approved. I show that limited capacity is inconsistent with a hypothesis that the decision-maker's policy is to stimulate efforts, and I discuss possible decision-maker motivations that could lead to a limited capacity policy.
Keywords: C78; 330; refereeing; peer review